Annualized and cumulative returns on venture-backed public companies categorized by industry - Amir Shachmurove; Yochanan Shachmurove (The Journal of Entrepreneurial Finance and Business Ventures, 2004)
This paper investigates the actual performance of 2,895 Initial Public Offerings of companies that were backed by venture capital from 1968 through 1998. It seeks to refute the myth that investors demand very high annualized and cumulative rates of return to compensate for the risks they are taking by financing ventures. In fact, it argues that, based on historical statistics, the total returns of the venture capital market are reasonable given the level of risk. This is done by concentrating on sections of various types of industries that have been supported by venture capital.
Keywords: 650